Melting the Ice Curtain: the extraordinary story of citizen diplomacy on the Russia-Alaska frontier - Ramseur, David, author; University of Alaska Press, publisher (Colorado State University. Libraries, 2017)
Just five years after a Soviet missile blew a civilian airliner out of the sky over the North Pacific, an Alaska Airlines jet braved Cold War tensions to fly into tomorrow. Crossing the Bering Strait between Alaska and the Russian Far East, the 1988 Friendship Flight reunited Native peoples of common languages and cultures for the first time in four decades. It and other dramatic efforts to thaw what was known as the Ice Curtain launched a thirty-year era of perilous, yet prolific, progress. Melting the Ice Curtain tells the story of how inspiration, courage, and persistence by citizen-diplomats bridged a widening gap in superpower relations. David Ramseur was a first-hand witness to the danger and political intrigue, having flown on that first Friendship Flight, and having spent thirty years behind the scenes with some of Alaska's highest officials. As Alaska celebrates the 150th anniversary of its purchase, and as diplomatic ties with Russia become perilous, Melting the Ice Curtain shows that history might hold the best lessons for restoring diplomacy between nuclear neighbors; 'We are now at another critical turning point in our history. Melting the Ice Curtain tells a compelling story of the success of grassroots citizen diplomacy and details lessons for today's perilously poor relations between the world's superpowers. Ramseur is one of Alaska's experts on this topic and he offers valuable insights on how we may turn our challenges into opportunities'--Russell J. Handy, Lieutenant General, USAF, Retired Commander, Alaskan Command.--Provided by publisher.
Maps -- Prologue -- A call to arms -- Extending hands of friendship -- A Juneau peacenik in the Kremlin -- Swimming against the current -- Historic flight approved -- Friendship flight to tomorrow -- Dramatic reversal -- Soviets return the favor -- Breaking the ice -- Adventure diplomacy across the Strait -- Deception on Diomede -- From Uelen to Vladivostok -- Visa-free reunification -- Golden Samovar Service -- Open for business -- Beyond the coup -- University of Alaska teaches Capitalism 101 -- Oil in Sakhalin, flush toilets in Chukotka -- The thrill is gone -- Mercy mission to Magadan -- Always keep talking -- Detained in the Bering Strait -- A special Alaska-Russia affinity.
Keywords: Alaska -- Relations -- Soviet Union; Soviet Union -- Relations -- Alaska; Alaska -- Boundaries -- Soviet Union; Soviet Union -- Boundaries -- Alaska; Diplomacy -- History -- 20th century; Alaska -- History -- 1959; Political participation -- History -- 20th century; Soviet Union -- Foreign relations -- 1985-1991; Friendship -- Political aspects -- History -- 20th century; United States -- Foreign relations -- 1981-1989